2022
DOI: 10.3390/su141912539
|View full text |Cite
|
Sign up to set email alerts
|

Is PET an Adequate Index to Determine Human Thermal Comfort in Mexico City?

Abstract: The urban heat island (UHI) is mostly due to urbanization. This phenomenon in concert with the high temperatures caused by global climate change may profoundly affect human thermal comfort, which can influence human productivity and morbidity especially in spring/summer period. The main objective of this investigation was to determine changes in degree of thermal comfort of Mexico City’s inhabitants and compare it with the physiological equivalent temperature (PET) to evaluate whether PET and its categorizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…It is important to carefully choose thermal comfort indices based on specific climatic conditions and consider relevant microclimatic variables to obtain more accurate assessments of outdoor thermal comfort. Several studies have been conducted to evaluate outdoor thermal comfort indices, including UTCI, PET, and SET, and their application in different climatic contexts [31][32][33][34][35][36]. These studies have highlighted the need to adjust thermal stress categories for a better evaluation of residents' thermal comfort, based on pedestrian thermal sensation data and on-site microclimatic data.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to carefully choose thermal comfort indices based on specific climatic conditions and consider relevant microclimatic variables to obtain more accurate assessments of outdoor thermal comfort. Several studies have been conducted to evaluate outdoor thermal comfort indices, including UTCI, PET, and SET, and their application in different climatic contexts [31][32][33][34][35][36]. These studies have highlighted the need to adjust thermal stress categories for a better evaluation of residents' thermal comfort, based on pedestrian thermal sensation data and on-site microclimatic data.…”
Section: Questionnairementioning
confidence: 99%
“…This study used microclimatic measurements and surveys on the thermal perception of space users. It emphasised the need to adjust thermal stress categories for a better assessment of residents' thermal comfort [34].…”
Section: Introductionmentioning
confidence: 99%
“…PET is based on typical indoor conditions, where the PET value in a comfortable response position is a measure of temperature where the wind is weak, there is no solar radiation, but it found thermal equilibrium in the human body, which can occur in a complex outdoor spaces. However some of authors have found that there were deviation between the PET calculation and from questionnaire (Ballinas et al, 2022;Iskandar et al, 2021). Another comfort index that commonly used in the study of comfort is PMV.…”
mentioning
confidence: 99%